One size does not fit all: the need for flexibility in policy responses to slow growth - Songqi Wang (China Finance and Economic Review, 2015)
The root cause behind the Chinese economy's slowing down in 2012 lies in a "one-size-fits-all" approach to macroeconomic management. This approach must be abandoned if domestic demand is to be effectively boosted. A superior approach would involve the introduction of policies tailored to the specific needs of the economy. It would call for some combination of fiscal and tax measures to stimulate investments, to enhance the profitability of non-Internet-based economic sectors, to ease lending restrictions, and to increase the growth rate of the money supply. There is little risk of inflation in China in the short term, but deflation is a real threat.
Keywords: 330; Macroeconomic management; Credit management; Deflation